A new insulin-sensitive enhancer from Silene viscidula, WPTS, treats type 2 diabetes by ameliorating insulin resistance, reducing dyslipidemia, and promoting proliferation of islet β cells. (March 2021) - Zhang, Caijuan; Qiao, Sanyang; Wu, Jiahui; Xu, Wenjuan; Ma, shuangshuang; Zhao, Baosheng; Wang, Xueyong
Graphical abstract: PI3K/AKT pathway is known as a critical signaling pathway that mediates the effect of insulin on anabolism and links lipid metabolism and insulin resistance. In this pathway, insulin is phosphorylated by IRS and activates PI3K to synthesize phosphatidylinositol (3, 4, 5)-trisphosphate (PIP3) when combined with the insulin receptor. PIP3 activates AKT via 3-phosphoinositide-dependent protein kinase 1 (PDPK1). Moreover, AKT stimulates the outer-membrane expression of GLUT4 in the cells, and GLUT4 promotes the peripheral tissues to utilize glucose, promote glycogen conversion, and decrease blood glucose levels. However, triacylglycerol further upregulates protein kinase C (PKC) expression. PKC inhibits IRS1 expression, leading to its inhibition via the PI3K/AKT pathway. The results showed that WPTS could downregulated the expression of Mogat1, Lipc, Smpd4, and Lpcat4 to inhibit triacylglycerol and it will weaken the inhibitory effect of PKC on IRS. At the same time, the expression of Irs1, PI3K, and Akt was upregulated to promote the expression of Glut4 and then promote the peripheral tissues to utilize glucose, promote glycogen conversion, and decrease blood glucose levels. Abstract: Wacao pentacyclic triterpenoid saponins (WPTS) is a newly discovered insulin sensitivity enhancer. It is a powerful hypoglycemic compound derived from Silene viscidula, which has a hypoglycemic effect similar to that of insulin. It can rapidly reduce blood glucose levels, normalizing them within 3 days of administration. However, its mechanism of action is completely different from that of insulin. Thus, we aimed to determine the pharmacological effects and mechanism of activity of WPTS on type 2 diabetes to elucidate the main reasons for its rapid effects. The results showed that WPTS could effectively improve insulin resistance in KKAy diabetic mice. Comparative transcriptomics showed that WPTS could upregulate the expression of insulin resistance-related genes such as glucose transporter type 4 ( Glut4 ), insulin receptor substrate 1 ( Irs1 ), Akt, and phosphoinositide 3-kinase ( PI3K ), and downregulate the expression of lipid metabolism-related genes such as monoacylglycerol O-acyltransferase 1 ( Moat1 ), lipase C (Lipc ), and sphingomyelin phosphodiesterase 4 ( Smpd4 ). The results indicated that the differentially expressed genes could regulate lipid metabolism via the PI3K/AKT metabolic pathway, and it is noteworthy that WPTS was found to upregulate Glut4 expression, decrease blood glucose levels, and attenuate insulin resistance via the PI3K/AKT pathway. Q-PCR and western blotting further validated the transcriptomics findings at the mRNA and protein levels, respectively. We believe that WPTS can achieve a rapid hypoglycemic effect by improving the lipid metabolism and insulin resistance of the diabetic KKAy mice. WPTS could be a very promising candidate drug for the treatment of diabetes and deserves further research.